Kinetics of in SITU transesterification using waste-derived catalyst for biodiesel production - Sulaiman, Sarina; Talha, Nur Syakirah; Balqis, Siti Noor (Penerbit Akademia Baru, 2017)
A kinetic study of in situ transesterification of solid coconut waste was conducted at 55-65°C. The mixing is kept constant at 350 rpm. The maximum conversion of 38.3% was obtained at 60°C, 1:10 solid to methanol ratio and 5 weight (wt.) % of catalyst. The feedstock was obtained after coconut milk extraction. The conversion of solid coconut waste to methyl esters was analyzed as function of temperature after 180 min of reaction. The experimental data appear to be a good fit into a pseudo first order kinetic model for the three stepwise reactions. The reaction rate constant, k and the activation energy, Ea were determined. In this study, the activation energy obtained from the experiment was 33.88 kJ/mol.